New multilevel inverter topology with minimum number of switches - Ahmed, R.A.; Mekhilef, Saad; Ping, H.W. (2010)
This paper presents two types of multilevel inverters, known as symmetrical and asymmetrical multilevel inverter. Both types are very effective and efficient for improving the quality of the inverter output voltage. Firstly, we describe briefly the structural parts of the inverter then switching strategy and operational principles of the proposed inverter are explained and operational topologies are given. The proposed topology reduces the number of switches, losses, installation area and converter cost. Finally, the simulation results are provided to validate the proposed theory.